The Portrayal of Women’s Power Ambivalence: in Literature- to- Film Adaptation of Enola Holmes - Bintang Priyanto Putri; Fatma Hetami; Rahayu Puji Haryanti; Widhiyanto Widhiyanto (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
The pursuit of dreams by women often results in a complex state of ambivalence, as they contend with societal, familial, and personal obstacles. This underscores the need for a new cultural narrative that reconciles the strengths and weaknesses of women. Our research focuses on examining the portrayal of woman's power in the novel and film Enola Holmes. Utilizing a qualitative approach and Betty Friedan's liberal feminism as a framework, we explore the multifaceted nature of female empowerment as represented by the character Enola Holmes. Our findings reveal that Enola's aspiration to become a detective symbolizes female empowerment but is marked by ambivalence. A form of ambivalence can be seen when Enola ends up in boarding school, falls in love with a man, gets help from male friend, gets a culture shock, and uses the name “Holmes”; Eudoria’s absence after her enthusiastic efforts of teaching Enola and making a plan for reform bill with her feminist movement; Dowager's plan to kill Tewkesbury is defeated by Enola Holmes and Tewkesbury; women oppressing women through the character Enola Holmes fights Edith and Enola Holmes argues Miss Harrison. Therefore, these complexities suggest a paradox: efforts to challenge patriarchal norms can inadvertently reinforce the culture they seek to change. In conclusion, our study highlights the nuanced nature of female empowerment in "Enola Holmes," offering insights into the intricate interplay between women's agency and societal norms in the ongoing struggle for gender equality.